A doubling of glacier mass loss in the Karlik Range, easternmost Tien Shan, between the periods 1972–2000 and 2000–2015. Issue 261 (23rd February 2021) - Wan, Zhujun; Wang, Yetang; Hou, Shugui; Huai, Baojuan; Liu, Qi
Abstract: Despite a number of studies reporting glacier extent changes and their response to climate change over the eastern Tien Shan, glacier mass-balance changes over multiple decades are still not well reconstructed. Here, glacier mass budgets on the Karlik Range, easternmost Tien Shan during the time spans of 1972–2000 and 2000–2015 are quantified using digital elevation models reconstructed from topographic maps, SRTM X-band radar data and ASTER images. The results exhibit significant glacier mass loss in the Karlik Range for the two time spans, with a mean mass loss of −0.19 ± 0.08 m w.e. a −1 for the 1972–2000 period and −0.45 ± 0.17 m w.e. a −1 for the 2000–2015 period. The doubling of mass loss over the latter period suggests an acceleration of glacier mass loss in the early 21st century. The accelerated mass loss is associated with regional warming whereas the decline in annual precipitation is not significant.